Water Quality a Priority for Profitable Fish Farming - Iqbal, Muhammad Naeem; Ashraf, Asfa (PSM Biological Research, 2020)
Fish farming has become increasingly popular in recent years, as a way of maintaining a sustainable food supply, especially in developing countries. Maintaining suitable water quality is critical to the success of a fish farm as the survival and optimum growth of cultured fish largely depend upon the good water quality. Setting up an effective and profitable fish farm requires an understanding of the water quality parameters for fish farming and how they impact fish life, the needs of the fish, and how to manage water quality parameters.